Adolescent health problems : behavioral perspectives - Wallander, Jan L.; Siegel, Lawrence J. (Advances in pediatric psychology, 1995)
Section I: General and conceptual issues * Epidemiology of adolescent health disorders / E. Wayne Holden and Katherine Nitz * Developmental influences on adolescent health / Aline G. Sayer, Stuart T. Hauser, Alan M. Jacobson, John B. Willett and Charlotte F. Cole * Theoretical models of adolescent risk-taking behavior / Susan G. Millstein and Vivien Igra * Legal issues in adolescent health care / Victoria P. Weisz and Gary B. Melton Section II: Current research and clinical perspectives on health-risk and prevention behaviors * Adolescent suicide attempters in general hospitals: Psychological evaluation and disposition planning / Anthony Spirito, James Overholser and Lyn Vinnick * Adolescents: The leading edge of the next wave of the HIV epidemic / Terry DiLorenzo and Karen Hein * Social-psychological antecedents and consequences of adolescent tobacco use / Laurie Chassin, Clark C. Presson and Steven J. Sherman * Coping and competence in adolescent alcohol and drug use / Thomas Ashby Wills, Donato Vaccaro and Gregory Benson * Health promotion with adolescents / Steven H. Kelder, Guy Parcel and Cheryl L. Perry Section III: Current research and clinical perspectives on chronic physical conditions * Appraisal, coping, and adjustment in adolescents with a physical disability / Jan L. Wallander and James W. Varni * Psychological adjustment of adolescents with cystic fibrosis or sickle cell disease and their mothers / Robert J. Thompson Jr., Kathryn E. Gustafson and Karen M. Gil * School-based treatment of recurrent headaches in adolescents / Bo Larsson * Managing insulin-dependent diabetes mellitus in adolescence: A developmental perspective / Suzanne Bennett Johnson * Family adaptation to diabetes: A model for intervention research / Tim Wysocki, Neil H. White, Jeanne Bubb, Michael A. Harris and Peggy Greco